99mTc-sestamibi SPECT/CT and 18F-FDG-PET/CT have similar performance but different imaging patterns in newly diagnosed multiple myeloma. Issue 10 (October 2020) - Mosci, Camila; Pericole, Fernando V.; Oliveira, Gislaine B.; Delamain, Marcia T.; Takahashi, Maria E.S.; Carvalheira, José Barreto C.; Etchebehere, Elba C.S.C.; Santos, Allan O.; Miranda, Eliana C. M.; Lima, Mariana C.L.; Amorim, Barbara J.; de Souza, Carmino A.; et al.
Abstract : Purpose: 18 F-fluorodeoxiglucose ( 18 F-FDG)-PET/CT has been widely used to evaluate multiple myeloma. 99m Tc-sestamibi (MIBI) scintigraphy has also been proposed for assessing multiple myeloma, but its use with state-of-the-art single-photon emission computed tomography/computed tomography (SPECT/CT) technology has not been fully evaluated.This study aimed to compare these two imaging modalities in multiple myeloma staging. Materials and methods: Sixty-two patients with recently diagnosed multiple myeloma were submitted to whole-body 18 F-FDG-PET/CT and whole-body MIBI scans plus SPECT/CT of the chest and abdomen/pelvis. Number of focal lesions, contiguous soft tissue involvement (CSTI), extramedullary lesions (EMLs) and diffuse bone marrow (BM) involvement were recorded. Results: PET/CT was positive in 59 patients (95%) and MIBI SPECT/CT in 58 (93%) ( P  = 0.69). MIBI detected more diffuse bone marrow involvement than PET/CT (respectively 78 vs. 58% of the patients), while PET/CT demonstrated more focal lesions than MIBI SPECT/CT (81 vs. 54% of the patients) ( P  = 0.002). PET/CT detected EMLs in four subjects and MIBI in one subject. CSTI was found in 28 (45%) and 23 (37%) patients on PET/CT and MIBI images, respectively ( P  = 0.36). Three patients with lytic lesions and no FDG uptake were MIBI positive, and two subjects with lytic lesions without MIBI uptake were FDG positive. Conclusion: MIBI SPECT/CT performs similarly to 18 F-FDG-PET/CT in identifying sites of active disease in multiple myeloma staging. MIBI is more efficient than FDG for detecting the diffuse involvement of bone marrow but less efficient for detecting focal lesions. Some patients presented a 'mismatch' pattern of FDG/MIBI uptake.